The effect of two stage solution treatment of Al6061 on its mechanical properties [compact disc] - 291770 Ismas Isurizazly Ismail (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan Mekanikal (Bahan)) - Universiti Teknologi Malaysia, 2005